Isolation and Identification of Î±-glycosidase Inhibitor Producer Endophytic Bacteria from Salak Pondoh Fruit (Salacca edulis) - Susilowati, Ari; Dewi, Citra Praba Yunita; Sari, Siti Lusi Arum (Biosaintifika: Journal of Biology & Biology Education, 2019)
Alpha-glycosidase inhibitors can delay the hydrolysis of oligosaccharide and disaccharide into glucose, which can prevent or treat hyperglycemia in diabetes mellitus. The rind and flesh of Salak Pondoh fruit are known to produce ?-glycosidase inhibitor compound. Endophytic bacteria that live in plant tissues potentially produce compounds such as in host plants. Exploration of endophytic bacteria from the rind and flesh of Salak Pondoh is one of the efforts to obtain isolates of bacteria producing ?-glycosidase inhibitors. The objective of this study is to isolate and identify endophytic bacteria producing inhibitor ?-glycosidase from rind and flesh of Salak Pondoh, and to know the activity of its ?-glycosidase inhibitor. Isolation of endophytic bacteria was done by inoculating surface-sterilized plant samples on Nutrient Agar (NA) medium. The inhibitory activity towards ?- glycosidase analysis was performed using the spectrophotometric method (? = 415 nm), with p-nitro phenyl ?-D-glucopyranoside as the substrate. Identification of the bacteria was performed based on the 16S rRNA gene sequence.  The sequencing was done at 1st Base Singapore and the obtained sequences were identified using the BLAST Nucleotide device on the NCBI website. In total, 6 bacterial isolates were obtained. The inhibitory activity ranged from 6.14-62.95% and the highest was generated by Kt-E isolates. The bacteria obtained were isolated Dt- A and Dt-B that represent genus Xanthomonas, Kt-E from genus Paenibacillus, Kt-I from genus Bacillus, Dm-A1 and Dm-A2 from family Enterobacteriaceae. The results confirm the potential of the endophyte bacteria of Salak Pondoh to be an alternative source of hyperglycemia medication.